Pancreatic Ultrasound in High-risk Neonates - Safaa A. ELMeneza; Naglaa F. Hassan; Aisha R. Mohamed (Общая реаниматология)
Pancreatic ultrasound is employed to assess the structure of the organ and diagnose various conditions. However, analyses of pancreatic images of high-risk newborn infants are scarce.Aim of the study: to investigate pancreatic echogenicity in high-risk neonates and evaluate the association between pancreatic echogenicity and clinical diagnosis.Materials and methods. This prospective observational case-control ultrasound study included 105 neonates admitted to the neonatal intensive care unit or outpatient. The patients were divided into two groups: group 1 (high-risk), which included 55 high-risk neonates, and group 2 (control), which included 50 neonates of comparable age with no history of high-risk pregnancy or delivery who were presented for medical consultation. Abdominal ultrasound examinations were performed, with a focus on the pancreas. Pancreatic echogenicity was classified as hyperechoic, isoechoic, or hypoechoic, relative to the liver.Results. No significant difference in pancreatic size was observed between the high-risk and control groups. A significant predominance of hyperechogenicity over hypoechogenicity or isoechogenicity was found in the high-risk group. A significant difference in echogenicity was found between the high-risk and control groups (P=0.0001). Neonates in the control group were more likely to have pancreatic isoechogenicity (60%) compared to hyperechogenicity (34%) or hypoechogenicity (6%). In the high-risk group, neonates had a higher frequency of pancreatic hyperechogenicity (72.72%) compared to hypoechogenicity (10.9%) or isoechogenicity (16.36%). Notably, 83.3% of infants born to diabetic mothers had a hypoechogenic pattern. Certain high-risk infants, such as preterm infants and those with perinatal asphyxia, had a higher frequency of hyperechogenicity (83.3%). The percentage of hypoechoic pattern was comparable in male and female newborns (50%); isoechoic pattern was more prevalent in females (77.3%) than in males (22.2%), while males had a more frequent hyperechoic pattern (57.5%).Conclusion. Evaluation of the pancreas in high-risk neonates and monitoring of long-term outcomes are of critical importance, especially in the infants of diabetic mothers.